Material híbrido para detecção de aminas aromáticas heterocíclicas - Rodrigues, Sueslley Gurgel Guimarães (2023)
Hybrid materials constituted of organic and inorganic substances have aroused the interest of the academic community in the proposition of analytical sensors for presenting properties that expand their application possibilities. More recently, materials containing biopolymers, such as chitosan, have been aligned with the global demand for biodegradable and less expensive products. The motivation of the present study is due to the possibility of using hybrid materials in the detection of heterocyclic aromatic amines (HAAs) produced during the processing of meat of animal origin, due to the association with the induction of some types of cancer. This work deals with the production of a hybrid material consisting of a chitosan film (organic portion) and the ion complex [Fe(CN)5(NH3)]3- (inorganic portion). The immobilization of the ion complex on the film was carried out through adsorption processes, being confirmed by electronic absorption spectroscopy in the UV-Vis regions through the observation of bands associated with charge transfer (~230 nm) and ligand field transitions (438 nm) and quantified (57.43 ± 0.86 μmol g-1) at 25 ºC by atomic absorption spectroscopy. The use of these hybrid matrices in the detection of HAAs is based on the reaction of replacing the NH3 ligand of the ion complex [Fe(CN)5(NH3)]3- by quinoxaline (IQx), the probe molecule used to mimic the interactions and interactions in real samples. The immersion of the hybrid matrix, both in aqueous solutions containing IQx and in hamburger samples doped with IQx, showed a color change from yellow to purple because of the absorption at 536 and 555 nm, respectively, indicating the feasibility of using it as a colorimetric sensor. Studies have shown that the histidine amino acid present in meat can be an interferer in the detection of HAAs, however, this does not present itself in a free form in solution, making this risk diminished. To use the hybrid matrices in environments outside the laboratory, paper strips were produced on which the hybrid matrices were deposited. The immersion of these strips in an aqueous solution of IQx showed the same color change, indicating that they can act as analytical sensors.